2013
DOI: 10.1111/jfpp.12085
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Processing Conditions to Improve the Rehydration and Sensory Properties of Freeze-Dried Cooked Rice

Abstract: This study investigated the effects of baking powder (BP) concentration, cooking temperature (CT) and freezing temperature on the rehydration ratio of freezedried cooked rice (FDCR). Rehydration ratios increased with higher BP concentration in soaking solutions, with 0.3% being considered the optimal concentration. Greater rehydration ratios were recorded at a CT of 120C than 100C. Rapid freezing (-70C) produced small intracellular ice crystals, whereas slow freezing (-20C) produced large ice crystals, causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…At room temperature being used as the soaking temperature, the increased baking powder concentration increased the rehydration capacity, however, the baking powder concentration of 0.3 and 0.5% was not different. This was in accordance with Song et al [ 3 ] who stated that the higher concentration of baking powder used, the higher the rehydration ratio of rice. This can be explained by the gas production of baking powder causing the space in the final QBJR structure after the drying process, which improves the rehydration capacity of the samples.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At room temperature being used as the soaking temperature, the increased baking powder concentration increased the rehydration capacity, however, the baking powder concentration of 0.3 and 0.5% was not different. This was in accordance with Song et al [ 3 ] who stated that the higher concentration of baking powder used, the higher the rehydration ratio of rice. This can be explained by the gas production of baking powder causing the space in the final QBJR structure after the drying process, which improves the rehydration capacity of the samples.…”
Section: Discussionsupporting
confidence: 92%
“…The physical properties and also microstructure of cooked rice has been improved by using baking powder [ 3 ] and also by adjusting the soaking temperature and soaking time [ 5 ]. The Quick Black Jasmine Rice were differently pretreated with baking powder solutions of 0.1, 0.3, or 0.5% at room temperature, 50, and 60 °C for 10, 20, and 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differing from the refrigerated cooked rice, most frozen cooked rice samples developed porous structures due to the formation of ice crystals during storage and exhibited a marked dependence on the storage temperature: the higher the temperature, the larger the pore size. Likewise, Song et al revealed that the pore sizes of freeze-dried cooked rice stored at −70 °C were smaller than those of the samples stored at −20 °C and −10 °C [ 40 ]. The difference in the porous structures may depend on the size distribution of ice crystals, and the latter is also closely related to the freezing rate [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%